1989
DOI: 10.1038/clpt.1989.90
|View full text |Cite
|
Sign up to set email alerts
|

Calcium antagonists in geriatric patients: Diltiazem in elderly persons with hypertension

Abstract: Pharmacodynamics and disposition of diltiazem were determined in twelve young (30 to 39 years of age) and twelve elderly (65 to 83 years of age) persons with hypertension after they had received diltiaz,em by rapid intravenous and long-term oral administration. Plasma disappearance half-life of diltiazem increased similarly and significantly in both groups with long-term dosing (young: rapid intravenous, 3.7 ± 0.8 hour; long-term oral, 6.3 ± 1 hour [mean ± SE]; elderly: rapid intravenous, 3.8 ± 0.7 hour; long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 0 publications
1
9
1
1
Order By: Relevance
“…Diltiazem induced no significant orthostatic reactions, which is in conformity with a recent report on both young and elderly hypertensive patients [17]. Nifedipine gave a marked increase in heart rate and virtually no increase in systolic blood pressure.…”
supporting
confidence: 70%
“…Diltiazem induced no significant orthostatic reactions, which is in conformity with a recent report on both young and elderly hypertensive patients [17]. Nifedipine gave a marked increase in heart rate and virtually no increase in systolic blood pressure.…”
supporting
confidence: 70%
“…These interindividual differences could be due to intersubject differences in the disposition and absolute systemic availability of diltiazem. Since the reported intersubject variation in the half-life of intravenous diltiazem is considerably smaller (Montamat et al 1989) than the variation observed here, the interindividual differences in steady-state plasma concentrations we observed probably resulted from variations in both elimination and first-pass metabolism.…”
Section: Discussioncontrasting
confidence: 46%
“…Therefore, the demonstration of mechanism-based CYP3A inactivation by nefazodone [111] coupled with knowledge of a major role for this enzyme in the biotransformation of nefazodone provide insight into the biochemical mechanisms of the nonlinear pharmacokinetics of this drug. Examples of other drugs that display nonstationary pharmacokinetics via autoinactivation of metabolic clearance include the SSRI antidepressant paroxetine [113], a substrate and inactivator of CYP2D6; the macrolide antibiotics erythromycin [114] and clarithromycin [115], and the calcium channel antagonists diltiazem [116] and verapamil [117] which are metabolized by and inactivate CYP3A; and the non-selective CYP substrate and inactivator ticlopidine [118].…”
Section: Implications For Clinical Study Design and Interpretationmentioning
confidence: 99%